VD_FINDINFO HC / 2013 / 20 vom 11. Januar 2013 - VD Tribunal cantonal (2013)
RETRAITVOIE DE DROIT, ASSISTANCE JUDICIAIRE | 106 al. 1 CPC (CH), 122 CPC (CH), 123 CPC (CH), 241 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)